ANALISIS PERUBAHAN PENUTUPAN LAHAN (LAND COVER) DI TAMAN WISATA ALAM SUNGAI LIKU KABUPATEN SAMBAS TAHUN 2013 - 2016 - AR, Yuda Silva; Latifah, Siti; Widiastuti, Tri (Universitas Tanjungpura, 2017)
Nature Tourism Park of Sungai Liku is one of the group of mangrove forests in the working area of Conservation Section Region III Singkawang which has a high potential to be developed into a tourist area of mangrove forest with a total area of 821, 30 hectares. Several cases in the management of the Nature Tourism Park are among other the presence of settlements and agricultural land in the area which are still going on, although the type and volume of wood are relatively small. The purpose of this study is to determine the changes in land cover of the Nature Taourism Park of Sungai Liku River in 2013-2016. The method used in this research was supervised classification, field ground check and analysis with the overlay technique on the data of Landsat imagery interpretation 8 OLI & TIRS coverage in 2013 and 2016.Changes in land cover of the Nature Tourism Park of Sungai Liku in Sambas Regency mostly happened in the class of rice which increased to 14,71 ha (1,95%). Followed by the open flooded which increased to 3,57 ha (0,47%), open dry increased to 0,15 ha (0,02%), and the beach area to 0,07 ha (0,01%). Land cover greatest decrease occurred in the land cover of secondary mangrove forest amounting to 14,71 ha (1,95%), and Shrubland area of 14,66 ha (1,95%), and followed by water body with an area of 1,92 ha (0,26%). Land cover class that have not changed from 2013 to 2016 is the land cover an area of CoastalForest of 2,33 ha (0,31%) in 2013 and 2016.Â Keywords: Land cover, Landsat images, Nature park.